Agent regret and the moral responsibility for the misuse of research results - Jan-Hendrik Heinrichs; Serap Ergin Aslan (Research Ethics Review)
An increasing number of research fields must expect that their projects will be classified as susceptible to misuse or otherwise security relevant, even if the reasons or criteria for this classification have not yet been uniformly developed. Research institutions will commonly distribute the obligation to predict and prevent misuse across multiple members and structures including ethics committees. However, cases of misuse occur even in spite of these precautions, raising the question of the type and distribution of responsibility for the resulting harm. This question becomes even more pressing if research ethics committees in their decisions ask researchers to provide a misuse- specific risk assessment or risk mitigation plan and thereby shift back a part of their responsibility on the researchers. While this kind of requirement may be considered as unsatisfactory by researchers, members of research ethics committees or boards and third-party funders, will argue that it fulfils two important functions. On the one hand, it makes use of the best available source for misuse risk-assessment available to most committees; on the other hand, it guarantees that the researchers at least try to take responsibility. If researchers, committee members and others involved discharge their obligation to predict and mitigate misuse risks with due diligence, any backward-looking responsibility they retain is to show agent regret for the results of their work having been misused.